2010
DOI: 10.1378/chest.09-0360
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Obesity and Obstructive Sleep Apnea

Abstract: Obstructive sleep apnea (OSA) adversely affects multiple organs and systems, with particular relevance to cardiovascular disease. Several conditions associated with OSA, such as high BP, insulin resistance, systemic infl ammation, visceral fat deposition, and dyslipidemia, are also present in other conditions closely related to OSA, such as obesity and reduced sleep duration. Weight loss has been accompanied by improvement in characteristics related not only to obesity but to OSA as well, suggesting that weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
374
1
13

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 668 publications
(411 citation statements)
references
References 113 publications
23
374
1
13
Order By: Relevance
“…A number of clinical trials have been conducted to evaluate the usefulness of dietary restriction in patients with OSA, and these have yielded mixed results. 3 Some weight loss, even of a relatively small amount, can lead to a decrease in the patient's AHI. Although the relationship between the amount of weight lost, and the decline in AHI, is not linear, overall, it appears that for each kilogramme lost, the AHI decreases by 0.6-1/ hour.…”
Section: Diet and Osamentioning
confidence: 99%
See 2 more Smart Citations
“…A number of clinical trials have been conducted to evaluate the usefulness of dietary restriction in patients with OSA, and these have yielded mixed results. 3 Some weight loss, even of a relatively small amount, can lead to a decrease in the patient's AHI. Although the relationship between the amount of weight lost, and the decline in AHI, is not linear, overall, it appears that for each kilogramme lost, the AHI decreases by 0.6-1/ hour.…”
Section: Diet and Osamentioning
confidence: 99%
“…26 Untreated OSA patients may have an increased appetite for refined carbohydrates, as well as increased ghrelin levels. 3 A recent trial comparing patients treated with diet alone, CPAP plus diet, and an oral appliance plus diet, found that only the group on CPAP therapy was able to lose a significant quantity of weight. 26 This suggests that CPAP therapy may be useful to treat OSA, and facilitate weight loss in these patients.…”
Section: Diet and Osamentioning
confidence: 99%
See 1 more Smart Citation
“…However, these contents were not taken into account in the present study. Weight loss is accompanied by improvements in characteristics related not only to obesity but also to OSA, suggesting that weight loss may be a cornerstone of the treatment of both conditions [24]. However, a relationship between weight reduction and OSA remission has not been demonstrated previously.…”
Section: Discussionmentioning
confidence: 96%
“…First, physical activity and dietary habits may be associated with metabolic disorders in OSA patients [5], thus these factors should be considered. In addition, confounding effects of gender difference and medications may also have influence in metabolic variables, and these factors should also be taken into account.…”
Section: Dear Editormentioning
confidence: 99%